Enhanced Rock Slope Stability Analysis: Integrating the Partial Factor Method into the Limit Equilibrium Method - Timalsina, Hare Ram (Journal of Engineering and Sciences, 2024)
Rock slope stability is crucial for sustainable design. Especially concerning natural or artificial rock-cut slopes. The stability of these slopes depends largely on features of rock mass, particularly discontinuities. Failure modes are determined by these features and are evaluated using kinematics analysis with stereographic projections. Various methods exist for analyzing rock slopes, including the limit equilibrium method (LEM), which assesses stability based on a factor of safety (FS). Conversely, the partial factor method (PFM), predominantly used in Europe, offers a more reliable and probabilistic approach, incorporating uncertainty factors. Although Eurocode, which employs the PFM, is widely utilized, it faces disputes and undergoes updates based on ISRM recommendations. The partial factor method is considered more conservative than the limit equilibrium method due to its comprehensive probabilistic approach. The choice between methods depends on project requirements, data availability, and expertise. This study compares the limit equilibrium and partial factor methods for rock slope analysis, concluding that the partial factor method is more conservative and sustainable for long-term stability assessment. Whereas, the traditional method is often used for short-term assessments.